2020
DOI: 10.1126/science.abc3710
|View full text |Cite
|
Sign up to set email alerts
|

Cell-cell adhesion in plant grafting is facilitated by β-1,4-glucanases

Abstract: Plant grafting is conducted for fruit and vegetable propagation, whereby a piece of living tissue is attached to another through cell-cell adhesion. However, graft compatibility limits combinations to closely related species, and the mechanism is poorly understood. We found that Nicotiana is capable of graft adhesion with a diverse range of angiosperms. Comparative transcriptomic analyses on graft combinations indicated that a subclade of β-1,4-glucanases secreted into the extracellular region facilitates cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 128 publications
(112 citation statements)
references
References 39 publications
2
110
0
Order By: Relevance
“…Development of new techniques for investigating wound response, such as MecWorm (Mithöfer et al, 2005) and SpitWorm that adds oral secretion to simulated herbivore-induced damage (Li G. et al, 2019), or laser-mediated wounding (Hoermayer and Friml, 2019;Marhavý et al, 2019) will help advance the field. Application of this newfound knowledge has the ability to improve grafting, regeneration, and crop production (Santamaria et al, 2013;Si et al, 2018;Coppola et al, 2019;Notaguchi et al, 2020;Zhang and Gleason, 2020).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Development of new techniques for investigating wound response, such as MecWorm (Mithöfer et al, 2005) and SpitWorm that adds oral secretion to simulated herbivore-induced damage (Li G. et al, 2019), or laser-mediated wounding (Hoermayer and Friml, 2019;Marhavý et al, 2019) will help advance the field. Application of this newfound knowledge has the ability to improve grafting, regeneration, and crop production (Santamaria et al, 2013;Si et al, 2018;Coppola et al, 2019;Notaguchi et al, 2020;Zhang and Gleason, 2020).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…We recently uncovered a key role of the GH9B3 clade of β-1,4-glucanases in cell-cell adhesion at the graft junction (Kurotani et al 2020;Notaguchi et al 2020). β-1,4-glucanases probably target cellulose in cell walls, and the overexpression of the β-1,4-glucanase gene promotes graft efficiency in Arabidopsis (Notaguchi et al 2020). In this study, we therefore tested whether exogenous application of cellulases facilitates graft adhesion using the Nb IVG system.…”
Section: Effect Of Cellulases On the Adhesion Of Nb Ivgmentioning
confidence: 99%
“…In regard to molecular mechanisms, studies have revealed the activity of enzymes, such as peroxidase and catalase, during grafting (Fernández-García et al 2004;Irisarri et al 2015;Pina and Errea 2008). Molecular genetic studies of grafting have been conducted in fruit trees, vegetables, and model plants (Chen et al 2017;Cookson et al 2014;Irisarri et al 2015;Kurotani et al 2020;Li et al 2016;Liu et al 2016;Matsuoka et al 2016Matsuoka et al , 2018Melnyk 2017;Melnyk et al 2015;Notaguchi et al 2020;Wang et al 2019;Wang et al 2014;Xie et al 2019). Among the various findings, these studies have clearly shown that grafting is promoted by auxin action through the expression of genes related to auxin signaling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations